Volatile profile of monofloral honeys produced in Brazilian semiarid region by stingless bees and key volatile compounds. (August 2018) - da Costa, Ana Caroliny Vieira; Sousa, Janaína Maria Barbosa; Bezerra, Taliana Kênia Alencar; da Silva, Flávio Luiz Honorato; Pastore, Gláucia Maria; da Silva, Maria Aparecida Azevedo Pereira; Madruga, Marta Suely
Abstract: The aim of this work was to characterize the volatile profile of monofloral honeys produced by Melipona subnitida (jandaíra) and Meliponas cutellaris (uruçu) from native floral sources that are typically found in the Brazilian semiarid region. The work also involved the optimization of the Headspace-Solid Phase Micro Extraction (HS-SPME) technique for volatile extraction using the response surface methodology. The botanical source had a strong influence on the volatile profile of the monofloral honeys produced by the two species of stingless bees from the semiarid region of Northeastern Brazil. The results obtained suggest the existence of differentiator compounds and potential markers for the botanical sources evaluated, such as linalool for malícia honey, D-sylvestrene for chanana honey, rose oxide for algaroba honey and benzenethanol for angico honey. The optimal conditions for the extraction of volatile compounds were as follows: equilibration time of 15 min, extraction time of 45 min and extraction temperature of 45 °C. Graphical abstract: Highlights: Volatile profile of honey from stingless bees from Caatinga bioma was reported for the first time. Optimization of the HS-SPME conditions for the extraction of the honey volatile fraction from stingless bees. Differentiation of honeys from different botanical origins was based on volatile compounds. Potential honey botanical origin markers were detected.